2019
DOI: 10.1002/adma.201807557
|View full text |Cite
|
Sign up to set email alerts
|

A Bioinspired Platform for Effective Delivery of Protein Therapeutics to the Central Nervous System

Abstract: Central nervous system (CNS) diseases are the leading cause of morbidity and mortality; their treatment, however, remains constrained by the blood–brain barrier (BBB) that impedes the access of most therapeutics to the brain. A CNS delivery platform for protein therapeutics, which is achieved by encapsulating the proteins within nanocapsules that contain choline and acetylcholine analogues, is reported herein. Mediated by nicotinic acetylcholine receptors and choline transporters, such nanocapsules can effecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(74 citation statements)
references
References 35 publications
3
71
0
Order By: Relevance
“…They also demonstrated that Ang2 peptide played a key role in the BBB penetrating by receptor-mediated transcytosis, as was reported in the previous studies [38]. The effect of EP-1 peptide to enhance BBB penetration might be due to the synergistic effect by adsorption-mediated transcytosis [44,45]. The enhanced BBB penetration of DOX encapsulated in the non-functionalized dendrimer might be due to the slightly positive charge on the dendrimer that could improve the adsorptionmediate transcytosis.…”
Section: In Vitro Evaluation Of the Bbb Penetration Of The Dual-targesupporting
confidence: 62%
See 1 more Smart Citation
“…They also demonstrated that Ang2 peptide played a key role in the BBB penetrating by receptor-mediated transcytosis, as was reported in the previous studies [38]. The effect of EP-1 peptide to enhance BBB penetration might be due to the synergistic effect by adsorption-mediated transcytosis [44,45]. The enhanced BBB penetration of DOX encapsulated in the non-functionalized dendrimer might be due to the slightly positive charge on the dendrimer that could improve the adsorptionmediate transcytosis.…”
Section: In Vitro Evaluation Of the Bbb Penetration Of The Dual-targesupporting
confidence: 62%
“…Therefore, nanocarriers were modified with various BBB-penetrating ligands to improve the receptor-mediated transcytosis and transporter-mediated transcytosis, which could enhance the ability of drug carriers across the BBB and deliver the therapeutic reagents into lesions without disrupting homeostasis and biological barriers [5]. Previous researches have determined several receptors and transporters for BBB penetrating by transcytosis, including low-density lipoprotein receptor-relative protein-1 (LRP1) [38,39], insulin receptor [40,41], transferrin receptor (TfR) [42,43], nicotinic acetylcholine receptor and choline transporter [44,45] and a short peptide (RVG29) derived from rabies virus [29,33]. Among these receptors, LRP1, a large multi-ligand endocytic receptor belonging to the low-density lipoprotein receptor family, has attracted wide interest in the therapy and diagnose of CNS disease.…”
Section: Ivyspringmentioning
confidence: 99%
“…Central nervous system (CNS) damage, including that caused by stroke, traumatic brain injury, and neurodegenerative disease, is the most prevalent cause of long-term disability and death [1,2]. A growing body of research has suggested that neuroinflammation is a major mechanism of CNS damage [3].…”
Section: Introductionmentioning
confidence: 99%
“…[26,27] As illustrated in Scheme 1C, 2-methacryloyloxyethyl phosphorylcholine (MPC), N-(3-aminopropyl) methacrylamide hydrochloride (APM), and N,N'-methylenebisacrylamide (BIS) are used as the monomers and crosslinker. These molecules are enriched around the catalase molecules through noncovalent interactions; [28,29] subsequent polymerization grows a thin polymeric shell around individual catalase molecules, forming nanocapsules denoted as n(CAT). The thin shell protects the enzyme, while allowing H 2 O 2 to rapidly transport through, endowing n(CAT) with high enzyme activity, augmented stability, and improved plasma half-life.…”
Section: Sars-cov-2 (Severe Acute Respiratory Syndrome Coronavirus 2)mentioning
confidence: 99%